A mixed study of the impacts of an IBA intervention on the vocabulary development of culturally and linguistically diverse students - Wessels, Stephanie (Kansas State University, 2008)
This quasi-experimental study was designed to measure the effects of a research-based intervention on fourth and fifth grade culturally and linguistically diverse students' vocabulary development. Through the extensive review of literature on vocabulary instruction and second language acquisition, a substantive theoretical framework titled the IBA Framework was developed. The IBA Framework incorporates characteristics of effective vocabulary instruction by accessing students' background knowledge, connecting unknown vocabulary words to known knowledge, ensuring opportunities for meaningful use of the vocabulary words, providing multiple exposures, and focusing on higher-level word knowledge. The IBA Framework also addresses second language acquisition by incorporating the linguistic, academic, cognitive, and sociocultural processes of the prism model. The IBA Intervention, derived from the IBA Framework, examined the affect of targeted vocabulary strategies on the overall vocabulary development of Culturally and Linguistically Diverse (CLD) students. Quantitative and qualitative methodologies were utilized for data collection and analysis. Quantitatively, the affect of the IBA Intervention was measured by the Measurement of Academic Progress (MAP) assessment and the Ecobehavioral System for the Contextual Recording of Interactional Bilingual Environments (ESCRIBE). MAP assessment scores were used to measure the overall literacy achievement of CLD students. Analysis of the data indicated that the treatment group made greater gains than the control group. ESCRIBE was used to measure students' overall engagement. The affect of the IBA Intervention was measured by combining the results of three student variables: language initiating/responding behaviors, oral responses, and activity-related responses. The overall engagement scores indicated that CLD students who received the IBA Intervention had higher levels of engagement than the control group. Qualitatively, the affect of the IBA Intervention on students' vocabulary retention was investigated using student documents, participant observation, and informal interviews. The emic perspective that emerged from the data suggested that students in the intervention group demonstrated their vocabulary retention by building vocabulary knowledge, clarifying vocabulary knowledge, extending vocabulary knowledge, and using vocabulary knowledge across settings. Exemplars from each of these categories were provided as evidence of the CLD students' attainment of a deeper level of permanent vocabulary knowledge.
Keywords: Vocabulary development; Culturally and linguistically diverse students; Student engagement; Education, Elementary (0524); Education, Language and Literature (0279); Education, Reading (0535)